Building A Thriving Learning Environment: A Guide To Education Management - K. Sunitha; Purvi Dagwale; Ruhani Kumari; Navdeep Singh Konsal (PT Agung Media Publisher, 2024)
This paper delves into the critical role of instructional design in cultivating thriving learning environments. It dissects two prominent pedagogical approaches: collaborative learning and direct instruction. The paper unpacks the theoretical foundations of each method. It explores the strengths of collaborative learning (fostering critical thinking, communication, problem-solving skills through social learning theory and constructivism), highlighting its ability to cultivate deeper understanding and increased motivation among students. However, the paper acknowledges potential challenges associated with collaborative learning, including management complexities and assessment difficulties. Conversely, the paper analyzes the merits of direct instruction. It emphasizes the effectiveness of this approach in establishing a strong foundation in fundamental skills and ensuring clear, consistent instruction. However, the paper recognizes potential drawbacks of direct instruction, such as limited student engagement and a potential neglect of higher-order thinking skills. Recognizing the influence of factors like student age, learning objectives, and subject matter, the paper underscores the importance of education managers strategically selecting the most appropriate approach. Ultimately, the paper advocates for a balanced approach that capitalizes on the strengths of both collaborative learning and direct instruction to create a dynamic and engaging learning experience, empowering students to develop essential 21st-century skills